DAMPAK ALIRAN MODAL ASING BAGI NEGARA-NEGARA BERKEMBANG: Proses âPerbaikanâ ataukah âPemburukanâ bagi Neraca Pembayaran - Purnomo, Didit (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2002)
Generally, foreign capital invested in developing countries function as externally additional capital resources in order to accelerate investment and economical growth, and also to mobilize capital as well as to transform economical structure. In this article, the writer discusses many impacts as a logical consequence of foreign capital inflows in some developing countries, including low income countries. Here, much discussion is talking about pros and cons arguments related to foreign capital inflows. The writer views that the abundance of foreign capital inflows in some developing countries mostly brings to negative impacts (from the view of balance sheet). To support his argument, the writer also put a "trivia hypothesis" such as: tightening rules about foreign capital inflows to make budget deficit not getting worse, reducing the structure of industrial sectors consisting many industrial sub sectors which is producing high-value added product and non-resources-based products and also not opening opportunity to posses as much 100 % for foreign investors.